AN EVALUATION OF ENGLISH COURSEBOOK FOR YOUNG LEARNERS ENTITLED ENGLISH CHEST - Nicolaus Henry Supriyanto (Widya Mandala Surabaya Catholic University, 2019)
One of the English coursebooks used in the teaching and learning English in Indonesia is English Chest. This study was conducted to answer the questions: (1) To what extent does English Chest series fulfill the criteria of a good English coursebook for young learners in terms of: physical format, subject matter, page layout, vocabulary and structure, graphic elements and content?; and (2) Does this coursebook meet the requirements of the syllabus of teaching English in primary school in Indonesia? The terms were developed and modified based on the criteria proposed by Varella (2014) about the good coursebook for young learners. The design of the study is descriptive qualitative. Ten English teachers using the coursebook were asked to assess it based on a checklist and interviewed. After the data were analyzed, the findings revealed that English Chest coursebook the series is categorized as a good and appropriate English coursebook for EFL young learners. Furthermore, the syllabus proposed by English Chest coursebook the series is in agreement with the syllabus of Kurikulum Tingkat Satuan Pendidikan 2006.